Bencana Kekeringan dalam Perspektif Mitigasi, Rehabilitasi, dan Rekonstruksi serta Dampaknya: Studi Komparatif antara Nusa Tenggara Barat dan Jerman - Danu Juliansyah; Ismazhenar Ismazhenar; Qisti Amlelia; Kayla Najiyah; Restu Noor Ramdani; Nida Nadira; Muhammad Adib; Ria Febrianti; Setio Galih Marlyono (Universitas Negeri Gorontalo, 2025)
Drought is a type of hydrometeorological disaster that is becoming increasingly frequent and severe due to global climate change. This phenomenon has a significant impact on food security, access to clean water, as well as social and economic stability, especially in highly vulnerable areas such as West Nusa Tenggara and temperate countries like Germany. This study aims to examine the characteristics of drought and its consequences in these two regions, review the effectiveness of mitigation and recovery measures that have been implemented, and assess the potential application of long-term risk management that can adapt to climate change. The method used is a systematic literature review by identifying, selecting, and synthesizing scientific articles and reports from relevant official institutions. From the analysis conducted, it was found that NTB faces chronic drought problems with limited water infrastructure and highly vulnerable social conditions, whereas Germany experiences severe drought due to prolonged rainfall shortages, impacting the agriculture, energy, and water resource sectors. Mitigation efforts in NTB still largely focus on emergency response and basic infrastructure development, while Germany implements a more comprehensive approach based on data and nature-based solutions. The opportunity to implement long-term risk management is considered highly dependent on the ability to integrate monitoring systems, strengthen local institutions, and adopt sustainable solutions. These findings emphasize the importance of an adaptive approach that balances structural interventions, preparedness, and inclusive water management.